Reclassifying the Turkish welfare regime in the light of child well-being indicators - Gürbüz, Didem. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
This study reexamines the welfare regime clustering of Turkey based on the data of child well-being across OECD countries between 2014 and 2017. In the previous literature, Turkish welfare regime is characterized as part of the Southern European (Spain, Portugal, Greece, and Italy) cluster. This thesis argues that the clustering of the Turkish welfare regime would be different from the previous literature’s finding, if child well-being indicators were taken into consideration. The thesis relies on the OECD’s following child well-being dimensions: material well-being, educational well-being, health and safety, risk behaviors. This thesis suggests that in terms of child well-being indicators, Turkey diverges from Southern Europe, and it resembles Latin American countries (Chile, Mexico, and Brazil). While a comparative analysis of social policy development in different countries lies beyond the scope of this thesis, the discussion presented in the study draws attention to the important role of family policies in determining the child well-being outcomes and suggests that gendered family policies appear as an essential factor affecting child well-being outcomes.
Keywords: Child welfare.; Welfare state -- Turkey.; Public welfare -- Turkey.